Combining Rosetta's GIADA and MIDAS data: morphological versus dynamical properties of dust at 67P/Churyumov–Gerasimenko. Issue 4 (12th September 2022) - Longobardo, A; Mannel, T; Kim, M; Fulle, M; Rotundi, A; Della Corte, V; Rinaldi, G; Lasue, J; Merouane, S; Cottin, H; Ciarniello, M; Dirri, F; et al.
ABSTRACT: We related morphological (size/shape) and dynamical properties of the dust ejected from the 67P/Churyumov–Gerasimenko comet by combining data from two instruments onboard the ESA's Rosetta mission, i.e. the MIDAS atomic force microscope and the GIADA dust detector. The two instruments detected dust of different size (10 −6 –10 −5 and 10 −4 –10 −3  m, respectively). MIDAS detected dust in four periods, three during the inbound orbit arc (2014 September–November; 2014 December– 2015 February; 2015 February–March) and one corresponding to a post-perihelion outburst (2016 February 19). For these periods, we analysed the dust particles' spatial distribution on the MIDAS targets to obtain the number of parent particles hitting the instrument by means of an empirical procedure and to measure the corresponding dust flux. For the same periods, we retrieved the dust flux measured by GIADA. The ratio between the two dust fluxes is constant. By coupling this result with activity models, we inferred that the particles detected by MIDAS are fragments of hundreds-micron- to mm-sized particles detected by GIADA. In addition, the similar dust flux ratios between nominal activity and outburst indicates that the outburst did not include micro- and nano-sized dust, differently from other outbursts previously observed. Dust and surface properties were related by applying a traceback algorithm to GIADA data to retrieve the source regions of dust ejected in different periods. We did not detect variations of morphological properties between dust ejected from more and less processed terrains, concluding that compact dust particles (detected by MIDAS) have the same properties across the comet surface.